Β‐Amyrin Biosynthesis: Effect of Steric Bulk at the 6‐, 10‐ and 15‐Positions in the 2, 3‐Oxidosqualene Backbone on Polycyclisation Cascades. Issue 2 (5th December 2016) - Terasawa, Yuri; Sasaki, Yusuke; Yamaguchi, Yuki; Takahashi, Kazunari; Hoshino, Tsutomu
Abstract : β‐Amyrin synthase incubation experiments have been conducted to determine the influence of steric effects at the 6‐, 10‐ and 15‐positions of 2, 3‐oxidosqualene on the polycyclisation pathway. Nor‐ and ethyl‐substituted oxidosqualene analogues were synthesised. Cyclisation of the ethyl‐substituted analogues did not occur, but the nor analogues underwent a polycyclisation cascade to yield fully cyclised products with 6/6/6/6/6‐fused pentacyclic scaffolds generated via a final oleanyl cation. Previously, we reported that 19‐ and 23‐ethyl‐substituted analogues underwent polycyclisation reactions. Therefore, the catalytic domain involved in earlier cyclisation steps is notably compact. In contrast, the catalytic domain in the later cyclisation steps is more loosely packed (less compact) to accommodate the bulky ethyl group. The reaction cavities for recognising branched methyl groups are discussed by comparing β‐amyrin synthase with other triterpene cyclases such as lanosterol and hopene synthases. Abstract : On the methyl binding sites in the reaction cavity of β‐amyrin synthase: the catalytic domain responsible for the earlier stages of the polycyclisation reaction is notably compact, whereas the domain for the later stages is relatively loosely packed.